Peran Laboratorium Dalam Penanganan COVID-19 - Mirna Rahmafindari (PROCEEDING UMSURABAYA, 2023)
AbstractIn order to reduce the severity of the disease and reduce the mortality rate due to COVID-19, it is necessary to take the right steps in handling COVID-19. Laboratory tests are important in supporting the diagnosis and assessing the prognosis of the disease. In addition, laboratory examinations are also needed to reduce the spread of disease, by tracing people who are in close contact with confirmed patients or after traveling in endemic areas with rapid tests or Real-time Polymerase Chain Reaction (RT-PCR) examinations.